The Meaningful Meaninglessness of Multiverse Movies Everything Everywhere All at Once (Daniel Kwan /Daniel Scheinert, US 2022), Camus, and Qoheleth - Johnston, Robert K. (Journal for Religion, Film and Media, 2025)
Until recently, in Western culture the “multiverse” has most typically been limited to the abstractions of theoretical physics or the imagination of comic-book writers. However, in Everything Everywhere All at Once (Daniel Kwan / Daniel Scheinert, US 2022), the multiverse functions differently, becoming a deeply affecting metaphor particularly suited to the Asian-American immigrant experience but also suited more generally to the absurdity and chaos of contemporary life. The multiverse functions inthe movie as a symbol of life’s vanity, its absurdity, which paradoxically throws both characters and viewers back on the need for kindness and love. After unpacking the film narrative, this article moves to an inter-textual dialogue with two philosophers who also note the need to recognize life’s meaninglessness in order to live meaningfully: Albert Camus and the unknown writer of Ecclesiastes.